In vitro oxidative stress regulatory potential of Citrullus colocynthis and Tephrosia apollinea - Rizvi Tania Shamim; Khan Abdul Latif; Ali Liaqat; Al-Mawali Narjis; Mabood Fazal; Hussain Javid; Adnan Muhammad; Al-Harrasi Ahmed (Acta Pharmaceutica)
The present study investigates the potential role of medicinal plants Citrullus colocynthis and Tephrosia apollinea in ameliorating the oxidative stress developed during the generation of reactive oxygen species. Organic extracts of different organs (leaf, stem and root) of these medicinal plants obtained in n-hexane, chloroform, n-butanol and water were assayed for radical scavenging, total antioxidant capacity, anti-lipid peroxidation and reduced glutathione. The total phenolic content (TPC) of both selected medicinal plants was also evaluated. The results indicated that extracts of T. apollinea leaf, stem and root have higher TPC compared to those of C. colocynthis. Similarly, the results of the present study revealed higher bioactivity of C. colocynthis than that of T. apollinea in various antioxidant assays. Various plant parts of each plant were also compared.